Cross-Cultural Differences in the Processing of Non-Verbal Affective Vocalizations by Japanese and Canadian Listeners - Koeda, Michihiko; Belin, Pascal; Hama, Tomoko; Masuda, Tadashi; Matsuura, Masato; Okubo, Yoshiro (Frontiers in Psychology, 2013)
The Montreal Affective Voices (MAVs) consist of a database of nonverbal affect bursts portrayed by Canadian actors, and high recognitions accuracies were observed in Canadian listeners. Whether listeners from other cultures would be as accurate is unclear. We tested for cross-cultural differences in perception of the MAVs: Japanese listeners were asked to rate the MAVs on several affective dimensions and ratings were compared to those obtained by Canadian listeners. Significant Group x Emotion interactions were observed for ratings of Intensity, Valence, and Arousal.　Whereas Intensity and Valence ratings did not differ across cultural groups for sad and happy vocalizations, they were significantly less intense and less negative in Japanese listeners for angry, disgusted, and fearful vocalizations. Similarly, pleased vocalizations were rated as less intense and less positive by Japanese listeners. These results demonstrate important cross-cultural differences in affective perception not just of nonverbal vocalizations expressing positive affect (Sauter et al, 2010), but also of vocalizations expressing basic negative emotions.